Kaji Eksperimental Penggunaan Biosolar B40 Terhadap Unjuk Kerja Mesin Dengan Menggunakan Variasi Tekanan Pengabutan Pada Nosel - Walter Valentino Sinaga; Romy Romy; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Biodiesel is an alternative fuel that can be used to replace fossil fuels such as Diesel, which are increasingly depleting. Biodiesel has a higher viscosity, density, and surface tension value than conventional fossil fuels. The level used by the Indonesian government is 20-30% Biodiesel content, which is then added with Diesel fuel. If the percentage level of Biodiesel is increased, there are several ways that can be used to improve engine performance, one of which is to adjust the fogging pressure. This study aims to determine the effect of increasing fuel injection pressure on diesel engine performance using Biosolar B40. The research was carried out by means of a diesel engine operated at a constant rotation of 900 rpm, and given a load of 2,500 kg/m2 to 15,000 kg/m2. To improve fuel atomization, the authors change the fogging pressure by rotating the adjusting screw contained in the fuel nozzle and then tested using an injector tester so that the pressure values are 110 bar, 120 bar, 130 bar, 140 bar, and 150 bar. The calculated parameters include Δh on the orifice, the volume of fuel used, fuel consumption time, and engine rpm. In the tests conducted, it was found that variations in injection pressure have an effect on engine performance parameters such as effective shaft power, brake mean effective pressure, thermal efficiency values, air fuel ratio, and specific fuel consumption which are better than standard pressure. Where for the best engine performance value at an injection pressure of 150 bar, with an effective shaft power of 3,775 kW at a maximum load of 15,000 kg/m2, the greatest value of bmep at a load of 15,000 kg/m2 is 665.415 N/m2, the best thermal efficiency at a load of 12,500 kg/m2 is 89.902 %, for a better air and fuel ratio with a value of 212.852 at a load of 2,500 kg/m2, and the smallest specific fuel consumption with a value of 0.0000235 kg/kW.s at a load of 12,500 kg/m2. Keywords: Injection Pressure, Biodiesel, B40, Engine Performance